OPTIMIZING MOBILE APP PERFORMANCE: A COMPREHENSIVE GUIDE - Sridhar Rao Muthineni, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
Mobile application performance optimization has become a critical factor in today's digital ecosystem, directly impacting user satisfaction and business success. This comprehensive article explores various aspects of mobile app performance, from fundamental metrics to future considerations. It covers essential performance indicators, including launch time, response time, memory usage, and network efficiency, providing developers with practical strategies for optimization. The article delves into efficient coding practices, emphasizing memory management and code optimization techniques while highlighting the importance of proper resource utilization. Network optimization strategies, including request handling and caching mechanisms, are examined alongside UI/UX performance considerations for creating responsive user experiences. It extends to performance monitoring and testing methodologies, ensuring consistent application behavior across different devices and conditions. Additionally, the article addresses emerging trends in mobile technology, including 5G integration, artificial intelligence applications, and cross-platform development considerations, preparing developers for future challenges in mobile app optimization.